Nitazoxanide mitigates methotrexate hepatotoxicity in rats: role in inhibiting apoptosis and regulating endoplasmic reticulum stress - Mahmoud, Nevertyty Mohamed; Elshazly, Shimaa M.; El-shaarawy, Fatma; Zaitone, Sawsan A.; Aldahish, Afaf A.; Ahmed, Gehan A.; Fawzy, Manal S.; Aloyouni, Sheka Yagub; Abed, Sally Y.; Saeedi, Tahani; El-Sayed, Shaimaa S. (Frontiers in Pharmacology, 2024)
Objectives: Hepatotoxicity is a severe outcome of methotrexate (MTX) therapy, limiting its clinical use and contributing to its related morbidity and mortality. This study investigated the hepatoprotective effects of nitazoxanide (NTZ), an antiprotozoal drug, against MTX-induced hepatotoxicity and whether endoplasmic reticulum (ER) stress-modulation underlies the expected beneficial effects of NTZ. Methods: Thirty-six rats were allocated to six groups, one control group and five MTX groups, where induction of hepatotoxicity was achieved via injecting MTX (20 mg/kg). Groups were assigned as MTX-vehicle, NTZ-100, and NTZ-200 groups (at 100 and 200 mg/kg/day, gavage, respectively), N-acetyl cysteine (NAC) group (500 mg/kg), and 4-phenyl butyric acid (4-PBA) group (150 mg/kg, i.p). Liver function enzymes in serum, hepatic oxidative stress, proinflammatory cytokines, apoptosis, and ER-stress biomarkers were assessed. A histopathological examination was performed. Results: Treatment with NTZ lessened the serum liver enzymes, reduced malondialdehyde (lipid peroxidation product), enhanced antioxidant capacity, attenuated proinflammatory cytokines, and suppressed apoptosis. The protective effect of NTZ was dose-dependent, and the findings observed with the high-dose NTZ were similar to those obtained with the ER-stress inhibitor (4-PBA). Conclusion: NTZ exerted a hepatoprotective effect in MTX-challenged rats that is mediated via modulation of ER stress and inhibiting apoptosis.